Magnesium levels in AIDS-associated tuberculosis or cryptococcosis patients, and relationship with treatment response - Ronceros, Gerardo (2002)
OBJECTIVE: To demostrate that human immunodeficiency virus (HIV) patients in acquired immunodeficiency syndrome (AIDS) phase associated with tuberculosis (TB) or cryptococcosis have hypomagnesemia-related inadequate treatment response. DESIGN: Prospective and longitudinal study. MATERIALS AND METHODS: We studied 300 subjects, divided in six groups of 50 patients each: positive HIV patients, TB patients, AIDS patients with TB, AIDS patients with cryptococcosis, no-AIDS patients with acute infections and a normal group (blood donors). RESULTS: Average magnesium values were below normal in the groups AIDS/TB, AIDS/cryptococcosis and TB. There were important statistical differences in magnesium levels in the groups HIV, AIDS/TB, AIDS/ cryptococcosis and TB. With respect to hypomagnesemia, the group with less response to treatment was the AIDS+TB (27%). CONCLUSIONS: Hypomagnesemia is prevalent in chronic infectious diseases with important differences in magnesium levels among the four groups studied and AIDS/TB group showing more abnormalities.